Pelaksanaan Program Directly Observed Treatment Short-Course (DOTS) Selama Pandemi COVID-19 di Wilayah Puskesmas Depok Jaya - Alfaiza, Salsha Nur; Wuryaningsih, Caroline Endah (Perilaku dan Promosi Kesehatan : Indonesian Journal of Health Promotion and Behavior, 2022)
Background. TB is a problem in Indonesia. The government has implemented DOTS to reduce morbidity and mortality but hasn’t yet reached the target. During the pandemic, DOTS was being held with adjustments to input and process management. Purpose. Find out the description of the implementation of DOTS during a pandemic in the Puskesmas Depok Jaya area. Methods. This study used a qualitative case study design. Data collection techniques were in-depth interviews with the main informants, the PIC of DOTS, the doctor in charge of DOTS, the head of the cadre and 2 medication supervisors, the supporting informants were 4 tuberculosis patients. Researchers collected data by in-depth interviews online via Zoom. Results. Several main activities at the Puskesmas during the pandemic experienced a decrease in the number of activities, including contact investigations, screening, and training. There were several problems that occurred during the pandemic, the community was less open, had high mobility, so Puskesmas officers and health cadres had difficulties in carrying out monitoring related to contact investigations and treatment of TB patients. Conclusion. DOTS hasn’t run optimally due to a decrease in the number of activities.